2019
DOI: 10.1111/add.14577
|View full text |Cite|
|
Sign up to set email alerts
|

Tobacco control policies and smoking among older adults: a longitudinal analysis of 10 European countries

Abstract: Background and Aims The impact of tobacco control on European older adults has not been studied, despite evidence that smoking cessation at old age can bring significant life expectancy gains. Our aim was to evaluate the impact of tobacco control policies on smoking among older adults in Europe from 2004 to 2013. Design We used longitudinal data from the Survey of Health, Ageing and Retirement in Europe (SHARE, aged 50+ years) from four waves from 2004 to 2013. We used logistic regression models with clustered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…2 However, data from country-specific populations are poorly comparable, since they are not collected using a standardized study design-including sampling methods, mode of interviewing and questionnaires-which represents a prerequisite for valid comparisons of smoking prevalence and smoking patterns across different countries. 3,4 To the best of our knowledge, the only standardized and representative investigations that systematically monitor smoking prevalence among adults in more than one European country, are the WHO Global Adult Tobacco Survey (GATS) 5,6 ; the Survey of Health, Ageing and Retirement in Europe (SHARE) 7 ; and the European Commission (EC) Special Eurobarometers. [8][9][10] GATS covers three European Union (EU) member states (MS; ie, Greece, Poland, and Romania) 5,6 ; SHARE is a longitudinal study, conducted in five waves between 2004 and 2013, collecting information on smoking habit among individuals aged 50 years and older from 20 European countries 7 ; Eurobarometer is a representative survey conducted in all the 28 EU MS on approximately 1,000 face-to-face interviews per country, based on selected thematic studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, data from country-specific populations are poorly comparable, since they are not collected using a standardized study design-including sampling methods, mode of interviewing and questionnaires-which represents a prerequisite for valid comparisons of smoking prevalence and smoking patterns across different countries. 3,4 To the best of our knowledge, the only standardized and representative investigations that systematically monitor smoking prevalence among adults in more than one European country, are the WHO Global Adult Tobacco Survey (GATS) 5,6 ; the Survey of Health, Ageing and Retirement in Europe (SHARE) 7 ; and the European Commission (EC) Special Eurobarometers. [8][9][10] GATS covers three European Union (EU) member states (MS; ie, Greece, Poland, and Romania) 5,6 ; SHARE is a longitudinal study, conducted in five waves between 2004 and 2013, collecting information on smoking habit among individuals aged 50 years and older from 20 European countries 7 ; Eurobarometer is a representative survey conducted in all the 28 EU MS on approximately 1,000 face-to-face interviews per country, based on selected thematic studies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 To the best of our knowledge, the only standardized and representative investigations that systematically monitor smoking prevalence among adults in more than one European country, are the WHO Global Adult Tobacco Survey (GATS) 5,6 ; the Survey of Health, Ageing and Retirement in Europe (SHARE) 7 ; and the European Commission (EC) Special Eurobarometers. [8][9][10] GATS covers three European Union (EU) member states (MS; ie, Greece, Poland, and Romania) 5,6 ; SHARE is a longitudinal study, conducted in five waves between 2004 and 2013, collecting information on smoking habit among individuals aged 50 years and older from 20 European countries 7 ; Eurobarometer is a representative survey conducted in all the 28 EU MS on approximately 1,000 face-to-face interviews per country, based on selected thematic studies. The most recent Eurobarometer surveys focusing on tobacco smoking indicated that the overall smoking prevalence in the EU had slightly decreased from 29% in 2009 to 26% in 2014, and remained stable until 2017.…”
Section: Introductionmentioning
confidence: 99%
“…6 The World Health Organization supports the upward implementation to impose high tobacco taxes, driving up retail prices of the product, as the most effective tobacco control measure. 2,9,10 Higher retail prices have been found to reduce the prevalence of smoking in the older population at a rate of approximately 9% for every 1 USD increase. 10 However, the retail prices of tobacco across countries, especially those in Asia, have remained low.…”
Section: Introductionmentioning
confidence: 99%
“…We are grateful to Bethea Kleykamp for her interest in our study and for the highly relevant comments . We agree with her that the conclusion in the abstract of our article did not fully reflect our main findings, namely that Tobacco Control Policies (TCP) were not found to influence smoking among individuals older than 65 years. However, in the main text we described carefully how the negative relation found between TCP and smoking was driven by the reduction in smoking among those aged between 50 and 65, and not among those older than 65.…”
mentioning
confidence: 61%